ANALISIS HELPING BEHAVIOR DALAM PENYELENGGARAAN DIKLAT DI BALAI DIKLAT KEAGAMAAN BANDUNG (Suatu Pendekatan Teori Organizational Citizenship Behavior) - Ranti Nuranita (Balai Diklat Keagamaan Bandung, 2018)
In training management pro-social attitudes needed by all employees as the organization good citizens such as: employees sincerely work full-heartedly to develop the organization and are willing to work beyond their own jobs and functions as the representation of virtuous. These behaviors are necessary for the education and training management in order to be qualified and run smoothly and optimally. These behaviors are known as organizational citizenship behavior (OCB). This research employed a descriptive qualitative method, and the purpose of this research was to examine how the employee organizational citizenship behaviors specialy helping behavior took place in the education and training management at Bandung Religious Training Centre. It also tried to provide recommendations so that the employee organizational citizenship behaviors at Bandung Religious Training Centre continuously improved to increase the quality of education and training administration. The research findings that, in the education and training management, the employees have not showed the criteria of helping behavior. It is recommended that to raise the employee helping behaviors, and change the employees’ mindset, develop the positive values of helping behaviors, improve the employee competence through TOC and MOT Training, and change the existing leadership style into horizontal leadership.Key words: OCB, helping behavior, training management.